Larvicidal Potential of Red Fruit Extract (Pandanus conoideus Lamk.) Against Anopheles Larvae: A Pilot Study - Asrianto Asrianto; Rina Purwati; Eka Sari Gasela; Indra Taufik Sahli; Risda Hartati; Fajar Bakti Kurniawan; Afika Herma Wardani; Fachruddin Fachruddin (Jurnal Kesehatan Metro Sai Wawai, 2026)
Malaria continues to be a persistent public health issue, particularly in endemic regions such as Papua, Indonesia. Targeting mosquito larvae offers a practical point of intervention, especially in areas where breeding sites are accessible. In recent years, plant-derived compounds have gained attention as alternative larvicides, including red fruit (Pandanus conoideus), which is known to contain bioactive constituents with potential insecticidal properties. This study evaluated the larvicidal activity of ethanol and hexane fractions of red fruit extract against Anopheles larvae. A true experimental design with a completely randomised approach was applied. Extracts were prepared through ethanol maceration followed by fractionation. Larvae were exposed to five concentrations (0, 125, 250, 500, and 1000 ppm), and mortality was recorded at 60, 120, 180, and 240 minutes. Data were analysed using nonparametric tests, including the Kruskal–Wallis and Mann–Whitney U tests. Both ethanol and hexane fractions induced substantial larval mortality, with complete mortality observed at 240 minutes across all concentrations. Mortality increased progressively over time, while differences between concentrations and solvent fractions were not statistically significant (p > 0.05), suggesting a similar level of effectiveness under the experimental conditions. The findings indicate that red fruit extract possesses strong larvicidal activity against Anopheles larvae. The observed pattern suggests that exposure duration may play a more prominent role than concentration or solvent fraction in determining mortality outcomes. Further investigation is needed to explore dose–response relationships and assess performance under extended exposure and field conditions.